Evaluation of Two Malaria Surveillance Systems in Yemen Using Updated CDC Guidelines: Lessons Learned and Future Perspectives - Labiba Saeed Anam MD; Moamer Mohamed Badi MD; Methaq Abdullah Assada; Abdelwahed Abdelgabar Al Serouri PhD (SAGE Publishing, 2019)
Yemen is classified as high malaria endemic area with two-thirds of population at risk. Currently, the National Malaria Control Program (NMCP) uses two malaria surveillance systems: the Integrated Malaria Surveillance System (IMSS) and the Early Disease Electronic Warning System (eDEWS). This study aimed to assess and compare the usefulness and attributes of the two malaria surveillance systems. The systems were evaluated according to the US Centers for Disease Control and Prevention (CDC) updated guidelines. Data were collected from 10 stakeholders through interviews and from 10 districts' coordinators and 20 health facilities' focal points using semistructured questionnaire. The score of the system attributes were interpreted as very poor, poor, average, good, and excellent according to the mean percent score. Both systems were found to be useful. The IMSS overall performance score was poor where flexibility was average and simplicity, acceptability, representativeness, and stability were poor. For eDEWS, the overall performance score was good where data quality, acceptability, and flexibility were excellent; simplicity was good; representativeness was average; and stability was poor. In conclusion, although the IMSS was found to be useful for assessing the burden of malaria, response to outbreak, and future planning, the overall performance was poor. While the eDEWS overall level of performance was good, it was found to be useful only for outbreak detection. Therefore, both surveillance systems need to be integrated for the advantages of both systems to be maintained.